Effective Stakeholder Knowledge Sharing for Effective Organizational Memory - Ensign, Prescott C.; Robinson, Nicholas P. (Université d'Ottawa | University of Ottawa, 2009)
This chapter argues that a trusting corporate culture predicated on values that emphasize sharing and encourage interactions amongst stakeholders at all levels spawns knowledge sharing activities and leads to the development of robust organizational memory reserves. The authors argue that the importance of knowledge management in the information age will make it essential that competitive companies inculcate stakeholders with the values necessary to encourage the production, sharing, and storage of knowledge for the benefit of the organization and its stakeholders. The authors demonstrate that having the proper systems and processes in place and fostering a culture that values sharing should help organizations to develop and use latent knowledge reserves. An experiential learning model is used to illustrate how mere data can be transformed into commercially viable knowledge.